Hubungan antara Efikasi Diri dengan Minat Belajar Peserta Didik Bina Insan Cendekia (BIC) di Madrasah Aliyah Negeri 1 Jember - Laila Anjumil Musyarrofah (Fakultas Dakwah UIN KHAS Jember, 2022)
According to Bandura, self-efficacy is self-confidence that encourages individuals to learn by influencing achievement and motivation. Meanwhile, Santrock said that self-efficacy is an individual's belief in controlling a situation so as to achieve positive results. Not only self-efficacy that must be grown in students but also interest in learning, because with an interest in learning, it will be easier for him to absorb his knowledge. Basically, interest in learning does not develop by itself but must be nurtured and maintained by educators. The focus of the problem studied in this thesis is whether there is a significant relationship between self-efficacy and interest in learning for Bina Insan Scholar (BIC) students at Madrasah Aliyah Negeri 1 Jember. To identify these problems, this research uses quantitative research methods with a correlation research approach and survey research types. The data collection techniques through questionnaires, observation and documentation. This study concluded that BIC students at Madrasah Aliyah Negeri 1 Jember had a self-efficacy group, there were 9 people in the low group, 54 people in the medium group, and 10 people in the high group. While the learning interest group there are 11 people who fall into the low group, 48 people in the medium group, and 14 people in the high group. And for the results of the research hypothesis, it is known that the Pearson correlation value is 0.699, it can be stated that there is a significant relationship between self-efficacy and interest in learning which is included in the category of strong and positive correlation.